J. OCKMAN (ed) - Architecture School. Three Centuries of Educating Architects in North America - Valdivieso, Alejandro (ZARCH, 2016)
JOAN OCKMAN (ed) with REBECCA WILLIAMSON (research editor)Architecture School. Three Centuries of Educating Architects in North AmericaMIT Press, Cambridge, Massachusetts -London, England, 2012 / Association of Collegiate Schools of Architecture, Washington D.C., 400 págs.54,95 $. Idioma: inglés (tapa dura)